If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7f + -3 = 39 Reorder the terms: -3 + 7f = 39 Solving -3 + 7f = 39 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 7f = 39 + 3 Combine like terms: -3 + 3 = 0 0 + 7f = 39 + 3 7f = 39 + 3 Combine like terms: 39 + 3 = 42 7f = 42 Divide each side by '7'. f = 6 Simplifying f = 6
| x-3/5=-1 | | 46-2=8 | | 3x^4-14x^2-24=0 | | 50e-1=799 | | y-(-5)=9x+18 | | a/8-2=8 | | 2-x/2=8-x/3 | | 4(g+8)+7+4g= | | 11k-5=61 | | 8y=2x-48 | | 15y+10=85 | | u^3=27 | | 2-x+9=3x+8 | | (x-45)+(x-45)+(x-45)+2x=540 | | 3n+12=52 | | -3y=2x+12 | | 3(1.2b-1)+36=4.2 | | f(1)=1.5n+6 | | 9x-1=-6x+11 | | 12=-13+4y | | 8x-2=-2x+18 | | 13y+3=16y | | 4/5x-9=35 | | 10y^2+21y+2=0 | | -8x^2-40x+3=0 | | 5ln(x-3)=10 | | 1/2n-3=2/3n-1 | | (x^2)+1x+19=0 | | (2+5i)(4+3i)=0 | | 42+10x=4x | | 3y=7-2y^2 | | (x^2)-1x-19=0 |